2017
DOI: 10.1016/j.solidstatesciences.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Rapid microwave-assisted preparation of binary and ternary transition metal sulfide compounds

Abstract: Rapid microwave-assisted preparation of binary and ternary transition metal sulfide compounds AbstractTransition metal chalcogenides are of interest for energy applications, including energy generation in photoelectrochemical cells and as electrodes for next-generation electrochemical energy storage.Synthetic routes for such chalcogenides typically involve extended heating at elevated temperatures for multiple weeks. We demonstrate here the feasibility of rapidly preparing select sulfide compounds in a matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…59,60 Butala et al demonstrated microwave preparation of Fe 1−x Co x S 2 and CuTi 2 S 4 , accelerating reaction times to less than 40 minutes. 61 The microwave electromagnetic field interacts strongly with the transition metal, selectively heating the metal powder and allowing the reaction to occur rapidly at metal sites before significant sublimation of the chalcogen. 11,15 Since chalcogens are usually weakly absorbing, they do not heat up as quickly, which is advantageous because of issues of pressure build-up in the ampoule.…”
Section: Transition Metal Chalcogenidesmentioning
confidence: 99%
“…59,60 Butala et al demonstrated microwave preparation of Fe 1−x Co x S 2 and CuTi 2 S 4 , accelerating reaction times to less than 40 minutes. 61 The microwave electromagnetic field interacts strongly with the transition metal, selectively heating the metal powder and allowing the reaction to occur rapidly at metal sites before significant sublimation of the chalcogen. 11,15 Since chalcogens are usually weakly absorbing, they do not heat up as quickly, which is advantageous because of issues of pressure build-up in the ampoule.…”
Section: Transition Metal Chalcogenidesmentioning
confidence: 99%
“…While a wide variety of synthetic methods have been developed to directly prepare nano‐sized oxide and binary sulfide materials, most ternary sulfides are prepared with a high‐temperature solid state synthesis that produces micron‐sized particles. [ 48–50 ] In these cases, nano‐sized particles must be obtained post‐synthesis through a mechanical ball milling process.…”
Section: Introductionmentioning
confidence: 99%
“…The complex nature of the interplay between dimensionality and electrocatalytic reactivity in dimensionally controlled chalcogenides remains to be fully unraveled. However, there are many examples of solid-state, , hydrothermal/solvothermal, , chemical vapor deposition, ionic liquid, and surfactant-assisted , methodologies for synthesizing dimensionally and compositionally controlled chalcogenide structures. Zhang et al synthesized the entire range of 0D–3D structures based on thioarsenate motifs in their work where polyvinylpyrrolidone, polyethylene glycol-400, and 1-hexadecyl-3-methylimidazolium chloride were used as surfactants to generate 0D [NH 4 ] 8 [Mn 2 As 4 S 16 ], 1D [Mn­(NH 3 ) 6 ]­[Mn 2 As 2 S 8 (N 2 H 4 )], 2D [enH]­[Cu 3 As 2 S 5 ], and 3D [NH 4 ]­[MnAs 3 S 6 ] .…”
Section: Synthetic Flexibilitymentioning
confidence: 99%
“…The complex nature of the interplay between dimensionality and electrocatalytic reactivity in dimensionally controlled chalcogenides remains to be fully unraveled. However, there are many examples of solid-state, 57,58 hydrothermal/solvothermal, 59,60 chemical vapor deposition, 61−63 ionic liquid, 64 and surfactant-assisted 65,66 67 Additional studies involving surfactants for the synthesis of chalcogenide materials extended this methodology to other new 2D selenidostannates, 68 oxosulfides, 69 chalcogenidogermanates, 70 and numerous others. 65,66 The successful linking of chalcogenide motifs through surfactant chemistry is a very promising route toward novel composites having dimensionality-directed physicochemical properties, and may therefore offer a low-cost and scalable alternative to existing solid-state synthetic methods.…”
Section: Synthetic Flexibilitymentioning
confidence: 99%